It Ain’t What You Do (But the Way That You Do It): Will Safety II Transform the Way We Do Patient Safety; Comment on “False Dawns and New Horizons in Patient Safety Research and Practice” - Rebecca Lawton (International Journal of Health Policy and Management, 2018)
Mannion and Braithwaite outline a new paradigm for studying and improving patient safety – Safety II. In this response, I argue that Safety I should not be dismissed simply because the safety management strategies that are developed and enacted in the name of Safety I are not always true to the original philosophy of ‘systems thinking.’